2008
DOI: 10.1074/jbc.m709330200
|View full text |Cite
|
Sign up to set email alerts
|

Store-operated Ca2+ Influx Causes Ca2+ Release from the Intracellular Ca2+ Channels That Is Required for T Cell Activation

Abstract: The precise control of many T cell functions relies on cytoso-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
61
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 47 publications
4
61
0
Order By: Relevance
“…Previous studies performed on Jurkat T cells, a human lymphoblastic leukemia T cell line, suggested that RyR may be involved in regulating Ca 2ϩ signaling in T cells (18 -24). We have previously shown that in Jurkat T cells, the RyR regulate SOCE by controlling Ca 2ϩ store refilling (19). However, the conclusions drawn from studies on Jurkat T cells cannot be extended to primary human T cells because the latter express type 1 RyR (RyR1) and type 2 RyR (RyR2), whereas Jurkat T cells express type 3 RyR (RyR3) (25).…”
mentioning
confidence: 79%
See 4 more Smart Citations
“…Previous studies performed on Jurkat T cells, a human lymphoblastic leukemia T cell line, suggested that RyR may be involved in regulating Ca 2ϩ signaling in T cells (18 -24). We have previously shown that in Jurkat T cells, the RyR regulate SOCE by controlling Ca 2ϩ store refilling (19). However, the conclusions drawn from studies on Jurkat T cells cannot be extended to primary human T cells because the latter express type 1 RyR (RyR1) and type 2 RyR (RyR2), whereas Jurkat T cells express type 3 RyR (RyR3) (25).…”
mentioning
confidence: 79%
“…Cell Proliferation Assay-A cell division track assay was performed using the CellTrace carboxyfluorescein diacetate succinimidyl ester (CFSE) cell proliferation kit (Invitrogen) as described previously (19). Briefly, resting T cells were washed, resuspended in PBS containing 4 M CFSE at a density of 1 ϫ 10 6 cells/ml, and incubated at 37°C for 10 min.…”
Section: ϫ⌬Cqmentioning
confidence: 99%
See 3 more Smart Citations